2022
DOI: 10.1039/d2dt02960j
|View full text |Cite
|
Sign up to set email alerts
|

AIE-active Ir(iii) complexes functionalised with a cationic Schiff base ligand: synthesis, photophysical properties and applications in photodynamic therapy

Abstract: Two AIE-active Ir(iii) cationic complexes containing Schiff base ligands were synthesised. Ir-2-N+ NPs are shown to be good PSs in vitro for PDT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…49 with excited-state lifetimes of 542 and 551 ns, respectively. 50 Here, the synthesized SM4 results in a microsecond range (0.81 μs) lifetime, indicating a significant improvement in the lifetime compared to previously reported compounds (Figure S18, ESI).…”
Section: Photophysical Propertiessupporting
confidence: 52%
See 3 more Smart Citations
“…49 with excited-state lifetimes of 542 and 551 ns, respectively. 50 Here, the synthesized SM4 results in a microsecond range (0.81 μs) lifetime, indicating a significant improvement in the lifetime compared to previously reported compounds (Figure S18, ESI).…”
Section: Photophysical Propertiessupporting
confidence: 52%
“…In a previous study, Li et al reported the AIE active iridium­(III) based PS1 and PS3 along with their NPs with lifetimes of 54 and 24 ns for PS1 and PS3, whereas the lifetimes of PS1 NPs and PS3 NPs are 63 and 32 ns, respectively . In 2022, Liu et al reported Ir-1-N + and Ir-2-N + with excited-state lifetimes of 542 and 551 ns, respectively . Here, the synthesized SM4 results in a microsecond range (0.81 μs) lifetime, indicating a significant improvement in the lifetime compared to previously reported compounds (Figure S18, ESI).…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…The fluorescence of PSs with aggregation-induced emission (AIE) properties is enhanced under the aggregation state, which could well solve the difficulties of traditional PSs in the clinical application of image-guided PDT. [30][31][32][33] Mitochondria-targeted metal-based PSs have been widely reported by many research groups, but their development is greatly limited due to the short irradiation wavelengths, which are generally less than 500 nm, severe photodamage, and low penetration depth. [34][35][36] It is well known that phosphorescent complexes with near-infrared (NIR) emission can not only increase the penetration depth of excitation light to biological tissue but also effectively avoid the interference of self-fluorescence of living tissue in vivo optical imaging.…”
Section: •−mentioning
confidence: 99%